Maintaining the Quality of Salak Cultivar Madu with Aloe vera Gel – Beeswax Coating - Darmawati, Emmy; Rika Permata Sari, Putri; Suro Mardjan, Sutrisno (Jurnal Hortikultura Indonesia (JHI), 2020)
Salak or snake fruit cultivar madu is a supreme salak which has a higher economic value than prime of salak pondoh. The skin of the fruit is thin, bigger shell, and more juicy flesh, making the pell dry out easily and the flesh of the fruit rot due to transpiration and fungi. The coating of aloe vera combined with beeswax is expected to maintain the quality of salak during the distribution. The aim of this research was study of the coating application made from aloe vera-beeswax on honey salak was. The concentration of aloe vera was 30% and beeswax was 3%. The coating was done by dipping method in the form of emulsion (composite) and bilayer. Bilayer application was done by dipping salak in the aloe vera solution, after being dry, dipping it again in the beeswax solution. Storage was carried out at room temperature without packaging. This study used a completely randomized design with no coating as a control. Aloe vera 30% combined with 3% beeswax was able to maintain the quality of salak at room temperature up to 8 days with a level of damage 32.38 % - 34.29% while control (without coating) reaching 55.24% and no drying of the fruit peels. Application of coating in the form of an emulsion gives better results and is significantly different in weight loss and skin discolouration so it is advisable to use an emulsion. Keywords: bilayer, dipping, emultion, room temperature.